COMMON CHARACTRERISTIC OF DICTIONARIES: CLASSIFICATIONS OF DICTIONARIES (Ustozlar uchun, 2026)
This article explores the common characteristics and classifications of dictionaries, highlighting their diverse functions and structures. It delves into various types of dictionaries, their purposes, and the criteria used for their classification, providing a comprehensive understanding of this essential linguistic resource.